دور نظام المعلومات في الذكاء الاستراتجي للمؤسسة - حياة, مناصري; ياسمين, تماسيني; تهاني, يوسف (unuversity of eloued- جامعة الوادي, 2023)
تهدف هذه الدراسة إلى التعرف على مدى قدرة الرقابة الجبائية والمحاسبية ودورها للحد من ظاهرة التهرب والغش الضريبي، من خلال معرفة الدور البارز الذي تلعبه الضرائب في المحافظة على موارد الدولة، حيث تعتبر الجباية وسيلة تمويلية ومتعددة الأدوار تستخدم لتسيير وتحقيق الأهداف المسطرة من طرف الدولة وقد خلصت هذه الدراسة إلى أن عدم فعالية النظام قد تعرضه لبعض المشاكل التي تقلل من مردوده وبالتالي تنعكس على خزينة العامة للدولة، حيث أن ظاهرة التهرب والغش الضريبي تعتبر من ابرز التحديات التي تواجه كيان الدولة في تطبيقاتها للسياسة الاقتصادية، وعليه فان مكافحة ظاهرة الغش والتهرب الضريبي ضرورة ملحة للسلطات المختصة، غير انه يتعين أن تكون ملمة بصورة واضحة عن حجم الظاهرتين لاتخاذ الحلول المناسبة ومن بين الحلول المعتمدة هي فرض رقابة جبائية فعالة بأدواتها المتنوعة، إلا أن نجاعة الرقابة الجبائية مرتبطة ارتباطا وثيقا بمعرفة المكلفين بالضريبة وبأهمية المعلومات المجمعة، لأنها تساعد على تحليل نقدي متميز لأحسن التصريحات المكتتبة من طرف المكلفين بالضريبة وهذا ما يؤدي إلى الانتقاء الجيد للملفات الواجب إخضاعها للرقابة الجبائية. The purpose of this study is to identify the extent of fiscal and accounting control and its role to reduce the phenomenon of tax evasion and fraud, by knowing the prominent role played by taxes in the preservation of state resources, where the collection is a means of funding and multiple roles used to conduct and achieve the goals imposed by the State. The study concluded that the ineffectiveness of the system has exposed it to some problems that reduce its return and thus reflected on the public treasury of the state. The phenomenon of tax evasion and fraud is one of the most important challenges facing the state entity in its applications of economic policy. Therefore, combating fraud and tax evasion There is an urgent need for the competent authorities, but they must be clearly aware of the size of the phenomena to take appropriate solutions. Among the solutions adopted are the imposition of effective penal control with their various tools. However, the effectiveness of tax control is closely related to the taxpayer's knowledge and the importance of tax For Omat collected, it helps to better written statements from the party in charge of critical analysis of outstanding tax and this leads to a good selection for the files to be controlled tax تهدف هذه الدراسة الى معرفة دور نظام المعلومات في الذكاء الاستراتيجي للمؤسسة من خلال دراسة عينة من موظفي مؤسسة اتصالات الجزائر الوادي، المغير حيث تم توزيع الاستبيان بشكل ورقي30استمارة قابلة للمعالجة الاحصائية وعند استرجاع الاستمارة تم تفريغها وتحليلها ببيانتها بالاعتماد على برنامج"spss "وقد اظهرت نتائج الدراسة انه يساعد نظام المعلومات في اتخاد القرارات داخل المؤسسة بالإضافة انه يساهم نظام المعلومات في نجاح الذكاء الاستراتيجي للمؤسسة محل الدراسة This study aims to know the role of the information system in the strategic intelligence of the organization through the study of a sample of the employees of the Algeria Telecom Corporation, ELoued ElMeghier, where the questionnaire was distributed in paper form, 30 forms subject to statistical treatment, and when the form was retrieved, it was emptied and analyzed with its data based on the "spss" program. The results of the study showed It helps the information system in making decisions within the institution, in addition to that the information system contributes to the success of the strategic intelligence of the institution under study.
Keywords: نظام ، نظام المعلومات، الذكاء الاستراتيجي، المعلومات، اتخاد القرارات; System, information system, strategic intelligence, information, decision making.